Cultural trends and community formation in a South African township: Sharpeville, 1943-1985. - Jeffrey, Ian (My University, 1991)
Thesis examines cultural expressions and community attachment, and their relation to each other, in the creation and maintenance of urban identity. In examining this, the thesis considers a number of key cultural forms in Sharpeville such as boxing, football, musicial performance, youth. gangs, and styles of dress. It argues that, conceptually, "community" is never static; rather it is a state of existence, a perception, for a grouping of people. At a given time they may consider themselves to be collectively part of or constitute a community; at another, their attachments may be to a different entity - the local neighbourhood, for example. The empirical data was derived mainly from primary sources although due to the historical time-period examined - namely 1943 to 1985 - there was some reference to secondary sources. The research involved mainly in-depth interviews and participant observation. By administering a questionnaire, "key" informants within the various cultural areas examined were identifed and interviewed at length, sometimes more than once. The thesis argues that "communities" only gain a sense of cohesion, "identity" and unity at certain specific historical moments; at other times the cultured focus within them may in fact express quite other meanings than those of "community" for their members. This identity is seen thus as both a product of the structural features which inform, influence and even dictate its direction as well as the responses and actions of the residents themselves, in shaping its outcome.
A Dissertation Submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts.
Keywords: Ethnology -- South Africa.; Urbanization -- South Africa.; Community development, Urban -- South Africa.; Sharpeville (South Africa) -- History.